Norswertianolin Promotes Cystathionine γ-Lyase Activity and Attenuates Renal Ischemia/Reperfusion Injury and Hypertension - Niu, Yaping; Du, Congkuo; Cui, Changting; Zhang, Haizeng; Deng, Yue; Cai, Jun; Chen, Zhenzhen; Geng, Bin (Frontiers in Pharmacology, 2021)
Cystathionine gamma-lyase (CSE)/hydrogen sulfide (H2S) plays a protective role in cardiovascular diseases including hypertension and ischemia/reperfusion (I/R) injury. This study was aimed to screen natural small molecule compounds that activate CSE activity and then evaluate its effect(s) on kidney I/R injury and hypertension. Applying computer molecular docking technology, we screened the natural small molecule compound norswertianolin (NW)-specific binding to CSE. Using the microscale thermophoresis technology, we confirmed that the Leu68 site was the essential hydrogen bond site of NW binding to CSE. NW supplementation significantly increased CSE expression and its activity for H2S generation both in vivo and in vitro. In the model of acute and long-term kidney I/R injury, NW pretreatment dramatically attenuated kidney damage, associated with decreasing blood urea nitrogen (BUN), serum creatinine (Cr) level, reactive oxygen species (ROS) production, and cleaved caspase 3 expression. In spontaneously hypertensive rats (SHRs), NW treatment also lowered blood pressure, the media/lumen ratio of the femoral artery, and the mRNA level of inflammatory cytokines. In conclusion, NW acts as a novel small molecular chemical compound CSE agonist, directly binding to CSE, heightening CSE generation–H2S activity, and then alleviating kidney I/R injury and hypertension. NW has a potential therapeutic merit for cardiovascular diseases.